PT Baasithu Boga Services PT Baasithu Boga Services Strategic Plan and Camp Management Services Company - Hendrawan Wicaksono; Sri Widyastuti; Zulkifli Zulkifli (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This academic journal is qualitative research on analyzing and making a strategic plan for the company PT BBS catering and camp services. PT BBS has an existing client market from oil and gas companies in remote areas with the challenges of declining production trends and intense competition. This study tries to see things that affect the business both internally and externally, using strategic analysis tools such as the IFE-EFE Matrix, Competitive Profile Matrix - CPM, Grand Matrix Strategy, and SWOT/TOWS Analysis. The determination of the priority of marketing and operational strategies is carried out by analyzing the Quantitive Strategic Planning Matrix - QSPM, while determining the priority of alternative material supply strategies is carried out by the Analytical Network Process - ANP. In the end, the Strategic Plan is formulated with the Balanced Score Card. The study result in PT BBS research conditions shows that the short-term strategy is conservative to maintain performance in the old market and long-term preparation to enter new markets and develop service products with careful feasibility calculations. To survive and thrive in the competition, a cost leadership strategy is applied and forms part of the technostructure of the organization with a focus on contractual mastery, marketing in new markets, and product and service development.